Official male two-word first names in Croatia in 2011 - Horvat, Joža (Onomástica desde América Latina, 2022)
The subject of the paper are male two-word first names registered in the population census of the Republic of Croatia conducted in 2011. Among approximately 5600 different first names with more than ten bearers registered that year we found 150 two-word first names. First the statistical data of the entire corpus of two-word first names are presented, and then the attention is paid to male two-word first names (N = 71). It is determined which male two-word first names had the most bearers and which of their components were the most frequent. The corpus is then analyzed from a linguistic point of view. In classifying the examples, the criterion of component combinations is applied (first attention is paid to the linguistic origin and then to the onomastic definition of the first name, which is more precise). Some peculiarities of the registered first names are also highlighted (e.g., the types of links between components are determined, etc.).